Photobonding of silk fibroin-based hydrogels to rabbit corneas - Gutierrez-Contreras, Rocio; Gallego-Muñoz, Patricia; De La Hoz, Andrés; Fernández-Gutierrez, Mar; Kochevar, Irene E.; Martínez-García, M. Carmen; Marcos, Susana (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionCorneal abrasions are common ocular injuries characterized by the loss of epithelial cells. Severe cases are often treated with amniotic membrane transplantation. However, as an allogenic tissue, it can trigger immune responses, it is scarce and costly, and may require suturing to the cornea. In this study, we propose and evaluate two silk fibroin-based hydrogels implanted in rabbit corneas with a sutureless photobonding technique as a surrogate for the amniotic membrane in corneal wound healing.MethodsSilk fibroin-based hydrogels were developed with polyethylene glycol (PEG) 300 or 3350. The hydrogels were stained with 0.01% Rose Bengal and photobonded to ex vivo de-epithelialized rabbit corneal strips using a custom-developed irradiation system (532 nm; 0.13 or 0.15 W/cm2 irradiance for 6.6 min). Bonding strength after 24 and 72 h under hydrated conditions was measured using a uniaxial stretcher, with five samples per experiment. An in vivo proof of concept study was also performed: hydrogels were implanted in four anesthetized rabbits that were euthanized immediately after photobonding for bonding assessment after 24 and 72 h in hydration. Two additional rabbits received in vivo implants, were clinically monitored for 15 and 30 days, and euthanized for histological evaluation.ResultsBonding strengths measured 24- or 72-h after irradiation at 0.13 or 0.15 W/cm2 of 532 nm light reached 2–3 N/cm2 for both types of Rose Bengal-stained hydrogels. In vivo bonding strength was consistent with the ex vivo results. At 15 and 30 days after the procedure, the corneas exhibited complete re-epithelialization beneath the hydrogel.ConclusionSilk fibroin-based hydrogels can be successfully bonded to ex vivo rabbit corneas using a sutureless photobonding technique, achieving high bonding strength. The in vivo proof-of-concept study demonstrated the feasibility of the surgical procedure and confirmed corneal re-epithelialization.